2007
DOI: 10.1038/nn1919
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of conditioning to ambiguous cues by pharmacogenetic inhibition of the dentate gyrus

Abstract: Serotonin receptor 1A knockout (Htr1a(KO)) mice show increased anxiety-related behavior in tests measuring innate avoidance. Here we demonstrate that Htr1a(KO) mice show enhanced fear conditioning to ambiguous conditioned stimuli, a hallmark of human anxiety. To examine the involvement of specific forebrain circuits in this phenotype, we developed a pharmacogenetic technique for the rapid tissue- and cell type-specific silencing of neural activity in vivo. Inhibition of neurons in the central nucleus of the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
126
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 48 publications
8
126
1
Order By: Relevance
“…Contrariwise, deleting the 5-HT1A-R only in adulthood had no effect on anxiety-like behavior. Using a simple pharmacological approach, the fear-bias to ambiguity was mimicked in nonmutant mice by treatment with a 5-HT1A-R antagonist (WAY 100635) during the third and fourth postnatal weeks (Tsetsenis et al, 2007). These data again speak to the importance of serotonin as a factor driving the development of the corticolimbic systems subserving the stress response later in life (for further discussion, see Ansorge et al, 2007;Gross and Hen, 2004;Hariri and Holmes, 2006).…”
Section: Role Of 5-ht1a Receptorsmentioning
confidence: 96%
See 2 more Smart Citations
“…Contrariwise, deleting the 5-HT1A-R only in adulthood had no effect on anxiety-like behavior. Using a simple pharmacological approach, the fear-bias to ambiguity was mimicked in nonmutant mice by treatment with a 5-HT1A-R antagonist (WAY 100635) during the third and fourth postnatal weeks (Tsetsenis et al, 2007). These data again speak to the importance of serotonin as a factor driving the development of the corticolimbic systems subserving the stress response later in life (for further discussion, see Ansorge et al, 2007;Gross and Hen, 2004;Hariri and Holmes, 2006).…”
Section: Role Of 5-ht1a Receptorsmentioning
confidence: 96%
“…Further extending the phenotypic profile of the 5-HT1A-R knockout mouse, Gross and colleagues have recently demonstrated that these mice have a fear bias towards environmental cues that are ambiguous predictors of trauma and which produce little fear in non-mutant mice (Klemenhagen et al, 2006;Tsetsenis et al, 2007). 5-HT1A-Rs are expressed on pyramidal neurons in the hippocampus (Chalmers and Watson, 1991;Clement et al, 1996;Khawaja, 1995;Kia et al, 1996aKia et al, , 1996bRaurich et al, 1999;Wright et al, 1995) where they exert an inhibitory action (Corradetti et al, 1998).…”
Section: Role Of 5-ht1a Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Partially reinforced cued fear discrimination was tested as previously described (Tsetsenis et al, 2007). Mice received a single training session in Cxt A (as above).…”
Section: Partially Reinforced Cued Fear Discriminationmentioning
confidence: 99%
“…Recently, the phenomenon of judgement bias has been investigated in several animal species, some being aimed at welfare assessment while others are more interested in judgement bias in animal models of human affective disorders [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%